Blood product usage and factors associated with transfusions in cats with hemoperitoneum: 33 cases (2018–2022) - Bunnell, Nicole; Blong, April; Kundu, Debosmita; Mochel, Jonathan Paul; Walton, Rebecca (Frontiers in Veterinary Science, 2023)
Objective – To evaluate blood product usage in cats with hemoperitoneum. To secondarily evaluate factors associated with transfusion administration and the outcome of cats with hemoperitoneum. Design – Retrospective study between the years 2018-2022. Setting – University veterinary teaching hospital and private practice hospital. Animals – 33 cats admitted to the hospital diagnosed with hemoperitoneum from January 2018 to September 2022. Measurements and main results – Medical records were retrospectively reviewed; signalment, point-of-care diagnostics, effusion characteristics, and transfusion administration information was recorded. The most common etiology associated with hemoperitoneum was neoplasia (51.5%). Fifty-one percent (51.5%) of cats received a blood transfusion during hospitalization with the majority of cats receiving multiple transfusion types (69%). The etiology of hemoperitoneum was not associated with receiving a transfusion (P = 0.28) Point-of-care diagnostics including packed cell volume (PCV), total solids (TS) and platelet count were not significantly associated with receiving a transfusion (P = 0.317, P = 0.11 and P = 0.82, respectively). The PCV and TS of the effusion was also not significantly associated with transfusions (P = 0.91 and P = 0.63, respectively). Sixteen cats (48%) survived to discharge. Transfusions were significantly associated with outcome and cats that received a transfusion were more likely to survive to discharge (P = 0.008). Conclusions – In conclusion, hemoperitoneum from a variety of etiologies in cats is associated with a high proportion of transfusions. None of the evaluated point-of-care diagnostics were associated with transfusion administration in this study. Cats that received a transfusion were more likely to survive to discharge.